NATURA FUTURA. Architecture in Satellite Territories. Rethinking Tradition from a Contemporary Perspective - Gómez, José Fernando (Artes: Architecture, Technology and Sustainability, 2026)
This article frames, architecture in satellite territories, as a design practice that redefines the relationship between tradition, territory, and contemporaneity. From this perspective, tradition is conceived as dynamic knowledge integrating memory, construction techniques, and ways of inhabiting, serving as a relevant resource for addressing current challenges. It also proposes a vision of architecture as a tool for territorial and social transformation, promoting context-linked design processes through the use of local materials, appropriate technologies, and active community participation. Sustainability is presented as an inherent condition of the territory, grounded in resource optimization, the circular economy, and the recovery of traditional construction knowledge. Finally, the text advocates for an architecture capable of reconciling universal design principles with the cultural, environmental, and social specificities of each location, resulting in resilient, contextualized interventions aimed at strengthening identity and fostering the sustainable development of these territories.
Keywords: Satellite cities; circular economy; rurality; local materials; traditional techniques